Long‐term photo‐identification study of fin whales in the Pelagos Sanctuary (NW Mediterranean) as a baseline for targeted conservation and mitigation measures - Zanardelli, Margherita; Airoldi, Sabina; Bérubé, Martine; Borsani, J. Fabrizio; Di‐Meglio, Nathalie; Gannier, Alexandre; Hammond, Philip S.; Jahoda, Maddalena; Lauriano, Giancarlo; Notarbartolo di Sciara, Giuseppe; Panigada, Simone (Aquatic conservation, 2022)
Historical abundance estimates are important for establishing baselines from which trends can be determined using more recent data. Long‐term studies based on photo‐identification were merged and used to estimate population size, survival rate and sex ratio (biopsy sampling) of fin whales in the North‐western Mediterranean. Merging four existing photo‐id catalogues yielded a Mediterranean catalogue with 507 individually identified fin whales. Ninety‐five (18.7%) individuals were resighted at least once during the study period (1990–2007): 71 whales were resighted in different years, 24 within the same season and 13 both in the same season and in different years. The number of resightings within‐season ranged from one to four, over periods from 1 to 90 days. Capture histories from these individuals were used in the capture–recapture analyses. Estimates of the animals present in the area each year between 1991 and 1995 through different modelling approaches were consistent: 900–1,000 from a POPAN open population model; 1,200 from a multi‐sample closed population model; and 900–1,100 from simple two‐sample closed population models for pairs of consecutive years, all with heavily overlapping 95% confidence intervals. The estimated apparent survival rate of 0.916 (95% CI = 0.773–0.972) was lower than expected, which may be linked to temporary or permanent emigration, or mortality possibly owing to ship strikes. Conservation and mitigation measures such as Important Marine Mammal Areas and Particularly Sensitive Sea Areas are presented and discussed.